Community stroke education practices in New York State designated stroke centres. (December 2019) - Williams, Olajide; Leighton-Herrmann Quinn, Ellyn; Colello, Anna; Perdomo, Crismely; Chong, Ji; Thompsen, Bill; Wyrick, Tiana; Brissette, Ian; Labovitz, Daniel
Objective: Community stroke education is a regulated, integral component of stroke systems of care. However, little is known about the types of activities conducted by hospitals. This study was designed to examine the annual requirement for community stroke education among New York State's 119 designated Primary Stroke Centres and identify areas for improvement that may have an implication on stroke outcomes. Design: Cross-sectional survey design Setting: All 119 New York State designated Primary Stroke Centres were invited to participate. Methods: Participating hospitals completed a 29-item online questionnaire assessing multiple domains related to community stroke education including hospital characteristics, allocated resources, implementation barriers, current community stroke education practices and willingness to adopt best practice guidelines. Data were analysed using univariate descriptive and chi-square statistics. Results: Eighty-eight percent of hospitals completed the survey (105/119). Respondents were mostly stroke coordinators and stroke directors. Stroke outreach education was conducted two to four times per year in 58% of the hospitals ( n = 69). Community stroke education included behavioural risk factor modification, the detection of stroke risk through screening and stroke preparedness education at health fairs. Although 95% of hospitals ( n = 98) reported using at least one best practice approach for these activities, evaluation was generally poor, with only about 23% ( n = 24) implementing outcome-specific assessments. Major barriers to stroke outreach were inadequate staffing, time constraints and lack of funding. Conclusion: Hospital-driven community stroke education efforts occur infrequently and are poorly evaluated. This component of stroke systems of care would benefit from guidelines from regulatory agencies, which currently do not exist.